2009
DOI: 10.1080/09540120903012551
|View full text |Cite
|
Sign up to set email alerts
|

Male sex workers in Moscow, Russia: a pilot study of demographics, substance use patterns, and prevalence of HIV-1 and sexually transmitted infections

Abstract: Background To explore demographic characteristics, substance use patters, and estimate the prevalence of sexually transmitted infections (STI) and high-risk behaviors among male sex workers (MSW) in Moscow and to assess the feasibility of prospective cohort recruitment and retention among this population. Methods Longitudinal study of 50 men with 6 month follow up period. Participants were recruited through venue based and snowball sampling. Results HIV prevalence at baseline was 16% and 1 male seroconvert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 14 publications
0
27
1
Order By: Relevance
“…MSW in our study reported high rate of UAI with the clients (60.4%), while their STI/HIV prevalence was lower than studies performed elsewhere 18 20–22. Although condom use among MSW in our study was inconsistent, it seems that the overall lower HIV burden in Israel in comparison to other countries23 and the high rate of circumcision may have reduced their odds of infection.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…MSW in our study reported high rate of UAI with the clients (60.4%), while their STI/HIV prevalence was lower than studies performed elsewhere 18 20–22. Although condom use among MSW in our study was inconsistent, it seems that the overall lower HIV burden in Israel in comparison to other countries23 and the high rate of circumcision may have reduced their odds of infection.…”
Section: Discussioncontrasting
confidence: 66%
“…After participants provided informed consent, they individually completed a 64-question anonymous survey, which was adopted from similar studies focusing on MSW,9 17 18 adjusted to the Israeli environment and previously piloted on eight MSW who had visited the Levinsky STI clinic (see web appendix 2 for study questionnaire). The questionnaire included personal characteristics of the participants, their sex trade and their non-commercialised sexual practices, substance-use habits, self-reported domestic violence, being abused as a child, incarceration history and previously diagnosed STI.…”
Section: Methodsmentioning
confidence: 99%
“…Also, while the authors noted that the majority of MSWs in the Abidjan area were MSM, they did not collect data on types of partner [34]. The contextual description from the authors is supported by evidence from other contexts where partners of MSWs are male [108, 109]. Concurrently, systematic review methods were applied; however, sensitivity analysis and meta-analyses were not utilized.…”
Section: Resultsmentioning
confidence: 99%
“…2 3 24 [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] Prospective and retrospective studies demonstrate that agonist outpatient opioid substitution therapy is safe and cost effective at reducing drug use, needle sharing, HIV and bloodborne virus transmission, overdose, criminal activity, health risks in pregnancy, and initiation into injecting. 24 201 212-217 Antiretroviral therapy and needle-syringe programmes enhance these benefits.…”
Section: Drug and Alcohol Dependencementioning
confidence: 99%